Water-splitting photocatalyst material and method for producing the same

Doping strontium titanate with scandium and magnesium forms a nanostep structure, enhancing quantum efficiency and stability in water-splitting photocatalysts, addressing the inefficiencies of conventional methods.

JP2025001305APending Publication Date: 2025-01-08TOYOTA JIDOSHA KK +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023100814
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2025-01-08

AI Technical Summary

Technical Problem

Conventional photocatalysts for water splitting have low quantum efficiency and lack a stable production method.

Method used

Doping strontium titanate with scandium and magnesium to create a nanostep structure, with a molar ratio of 1:1 to 1:4 and doping amounts of 0.1 mol% to 10 mol%, producing a water-splitting photocatalytic material with high quantum efficiency and stability.

Benefits of technology

The resulting photocatalytic material achieves high quantum efficiency and stability, with minimal variation due to variations in firing conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025001305000001_ABST
    Figure 2025001305000001_ABST
Patent Text Reader

Abstract

To provide a stable water-splitting photocatalyst material with high quantum efficiency and a method for producing the same.SOLUTION: The present invention relates to a water-splitting photocatalyst material containing strontium titanate, where the strontium titanate is doped with magnesium and scandium.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a water-splitting photocatalytic material and a method for producing the same. [Background technology]

[0002] Hydrogen gas is expected to be used as a clean next-generation fuel that does not produce carbon dioxide when burned. Hydrogen gas can be produced by the water decomposition reaction using light energy with a photocatalyst, so development of a photocatalyst that can efficiently induce the water decomposition reaction using light is underway.

[0003] For example, Patent Document 1 discloses a method for producing a core-shell type photocatalyst, which includes a step of irradiating an aqueous solution containing a semiconductor and a water-soluble transition metal peroxo complex with light, thereby coating at least a part of the semiconductor surface with an oxide or hydroxide of the transition metal produced by reduction of the water-soluble transition metal peroxo complex.

[0004] Patent Document 2 discloses strontium titanate particles having a metal compound having a metal atom and a hydrocarbon group bonded to the surface and having absorption at wavelengths of 450 nm and 750 nm in the visible absorption spectrum.

[0005] Non-Patent Document 1 discloses a photocatalyst in which oxides of Rh (rhodium), Cr (chromium), Co (cobalt), etc. are attached to the crystal plane of particles of a semiconductor (SrTiO3:Al) in which strontium titanate (SrTiO3) is doped with aluminum (Al), which has an (external) quantum efficiency of 96% in water splitting by irradiation with light of a wavelength of 350 nm to 360 nm. Note that the (external) quantum efficiency is the value obtained by dividing the number of reduced hydrogen atoms (= the number of hydrogen molecules generated × 2) by the number of irradiated photons, and hereinafter in this specification, "quantum efficiency" means the (external) quantum efficiency.

[0006] Patent Document 3 discloses semiconductor particles containing strontium titanate to which a co-catalyst has been added and which is used as a photocatalyst to induce a water-splitting reaction in which water molecules are split into oxygen molecules and hydrogen molecules upon exposure to light, the semiconductor particles being strontium titanate doped with scandium. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2015-071128 A [Patent Document 2] JP 2019-130509 A [Patent Document 3] JP 2023-051595 A [Non-patent literature]

[0008] [Non-Patent Document 1] T. Takata, 8 others, Nature, volume 581, pp. 411-414, 2020 Summary of the Invention [Problem to be solved by the invention]

[0009] However, the quantum efficiency of conventional photocatalysts has not yet reached a sufficient level. In addition, even for photocatalysts described in Non-Patent Document 1 as having high quantum efficiency, as shown in the reproduction experiment in Patent Document 3, a method for producing a stable photocatalyst has not yet been established.

[0010] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide a water-splitting photocatalyst material having high quantum efficiency and stability, and a method for producing the same. [Means for solving the problem]

[0011] As a result of extensive research, the inventors discovered that semiconductor particles obtained by doping strontium titanate with scandium and magnesium have stable high quantum efficiency with little variation as a water-splitting photocatalyst material, and thus completed the present invention.

[0012] The gist of the present invention is as follows. (1) A water-splitting photocatalyst material containing strontium titanate, in which the strontium titanate is doped with magnesium and scandium. (2) The water splitting photocatalyst material according to (1), wherein the molar ratio of doped magnesium to scandium is 1:1 to 1:4. (3) The water splitting photocatalytic material according to (1), in which the molar ratio of doped magnesium to scandium is 1:2. (4) The water splitting photocatalyst material according to any one of (1) to (3), wherein the total doping amount of magnesium and scandium is 0.1 mol % to 10 mol % based on the total number of moles of strontium titanate. (5) A water-splitting photocatalyst material according to any one of (1) to (4), in which strontium titanate doped with magnesium and scandium has a nanostep structure formed by exposing only 100 faces, and the average step width of the nanostep structure measured by SEM is 5 nm to 20 nm. (6) A method for producing a water-splitting photocatalyst material according to any one of (1) to (5), comprising mixing strontium titanate, scandium oxide and magnesium oxide in strontium chloride, calcining the mixture, and then washing the mixture. (7) A water-splitting photocatalyst comprising the water-splitting photocatalyst material according to any one of (1) to (5) and a co-catalyst added to the particle surface of the water-splitting photocatalyst material. Effect of the Invention

[0013] According to the present invention, there are provided a water-splitting photocatalyst material having high quantum efficiency and stability, and a method for producing the same. [Brief description of the drawings]

[0014] [Figure 1] 1 is a graph showing the results of quantum efficiency in Example 1 and Comparative Examples 2 and 3. [Diagram 2] 1 is a graph showing the relationship between the Sc doping amount and quantum efficiency in Examples 1 to 4 and Comparative Example 1. [Diagram 3] 1 is a graph showing the relationship between the amount of Mg doping and quantum efficiency in Examples 5 to 10. [Figure 4] 1 shows scanning electron microscope (SEM) photographs of crystals of Example 1 and Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Preferred embodiments of the present invention will now be described in detail. In this specification, the features of the present invention will be described with reference to the drawings as appropriate. In the drawings, the dimensions and shapes of each part are exaggerated for clarity, and the actual dimensions and shapes are not accurately depicted. Therefore, the technical scope of the present invention is not limited to the dimensions and shapes of each part shown in these drawings. The water splitting photocatalyst material and its manufacturing method of the present invention are not limited to the following embodiments, and can be embodied in various forms with modifications and improvements that can be made by those skilled in the art within the scope of the gist of the present invention.

[0016] The present invention relates to a water-splitting photocatalytic material containing strontium titanate, in which the strontium titanate is doped with magnesium and scandium.

[0017] In the present invention, the "water-splitting photocatalytic material" refers to a photocatalytic material in a water-splitting reaction in which water molecules are split into oxygen molecules (oxygen gas) and hydrogen molecules (hydrogen gas) by irradiation with light.

[0018] The water splitting photocatalytic material of the present invention contains strontium titanate (SrTiO3).

[0019] The strontium titanate of the present invention is a semiconductor particle that is doped with magnesium (Mg) and scandium (Sc).

[0020] The amount of magnesium (Mg) doped into strontium titanate is usually 10 mol % or less, preferably 0.1 mol % to 5 mol %, and more preferably 0.5 mol % to 2 mol %, based on the total number of moles of strontium titanate.

[0021] The amount of scandium (Sc) doped into strontium titanate is usually 20 mol % or less, preferably 0.1 mol % to 10 mol %, more preferably 0.5 mol % to 8 mol %, and even more preferably 0.5 mol % to 2 mol %, relative to the total number of moles of strontium titanate.

[0022] The molar ratio of magnesium to scandium (Mg:Sc) doped in strontium titanate is usually 1:1 to 1:4, preferably 1:2.

[0023] The total doping amount of magnesium and scandium doped into strontium titanate is usually 30 mol % or less, preferably 0.1 mol % to 15 mol %, more preferably 0.1 mol % to 10 mol %, and even more preferably 0.5 mol % to 10 mol %, based on the total number of moles of strontium titanate.

[0024] By adjusting the amounts of magnesium and scandium doped into strontium titanate as described above, it is possible to obtain a water-splitting photocatalyst material that has high quantum efficiency and stable low variation, even if there is variation in the firing temperature and time during production of the water-splitting photocatalyst material.

[0025] The magnesium- and scandium-doped strontium titanate in the water-splitting photocatalyst material of the present invention has a nanostep structure formed by exposing only 100 crystal faces, and the average step width of the nanostep structure measured by SEM is usually 5 nm to 20 nm, and preferably 5 nm to 10 nm.

[0026] The average step width measured by SEM is calculated by randomly selecting about 20 step widths that make up the nanostep structure in the SEM photograph and averaging the selected step widths. The step width is shown in the lower diagram of Figure 4B. The lower diagram of Figure 4B shows three step widths, and each step width is the distance between two arrows.

[0027] Strontium titanate in the water-splitting photocatalyst material of the present invention has a nanostep structure specified by the above-mentioned step width, resulting in a water-splitting photocatalyst material with high quantum efficiency and stable low variation.

[0028] The water-splitting photocatalyst material of the present invention can be produced by a flux method known in the art, for example, the method described in Patent Document 3, except that strontium titanate, a compound containing magnesium, for example, magnesium oxide (MgO), and a compound containing scandium, for example, scandium oxide (Sc2O3), are used as raw materials. The water-splitting photocatalyst material of the present invention can be produced, for example, as follows. First, strontium chloride (SrCl2), for example, strontium chloride in an amount of 5 to 15 times, for example, 10 times the total number of moles of strontium titanate, strontium titanate, scandium oxide, and magnesium oxide are introduced into an agate mortar, preferably with the ratio of strontium titanate, scandium oxide, and magnesium oxide adjusted to be as described above, and mixed, for example, usually for 20 minutes to 1 hour, for example, 30 minutes, using an agate mortar to grind and mix. Then, the mixture is fired. The firing conditions are not limited. The firing can be carried out, for example, in air. The firing temperature is not limited, but is usually 874°C (melting point of strontium chloride) to 2072°C (melting point of strontium titanate, scandium oxide, and magnesium oxide), preferably 1000°C to 1400°C, and more preferably 1150°C to 1200°C. The firing time is not limited, but is usually 5 hours to 30 hours, and preferably 10 hours to 15 hours. The fired mixture is then washed, for example, ultrasonically washed. The washing is carried out until chlorine (ions) are sufficiently removed, for example, by confirming that the pH of the washing water is about 7 and that the washing water does not react with silver nitrate.

[0029] In the method for producing a water-splitting photocatalyst material of the present invention, strontium chloride melts and becomes liquid during firing, and scandium and magnesium atoms are introduced and doped into the interior of strontium titanate in the liquid to produce Sc-Mg-SrTiO3 particles. By doping strontium titanate with magnesium and scandium using the method for producing a water-splitting photocatalyst material of the present invention, it is possible to produce a water-splitting photocatalyst material that has high quantum efficiency and is stable and has little variation, even if the firing temperature and time vary.

[0030] The water-splitting photocatalyst material of the present invention can be used as a water-splitting photocatalyst by adding a cocatalyst as described in Patent Document 3 or as described below. The water-splitting photocatalyst enables stable water splitting with high quantum efficiency.

[0031] The cocatalyst added to the surface of the magnesium- and scandium-doped strontium titanate particles may be any cocatalyst known in the art, and is not limited thereto. Examples of the cocatalyst include rhodium-chromium oxide (Rh / Cr2O3) and cobalt oxide hydroxide (CoOOH). It is believed that the cocatalyst prevents the charges (electrons and holes) generated by the irradiation of light in the semiconductor particles from moving back to the inside of the semiconductor particles after they have moved to the surface of the semiconductor particles in the light-induced water splitting reaction. The cocatalyst can be added to the surface of the semiconductor particles dispersed in water by photoelectrodeposition (photoprecipitation). Here, the photoelectrodeposition can be carried out as described in Patent Document 3 or in the Examples below. In the case of photoelectrodeposition, for example, the amounts of Rh, Cr, and Co are not limited, but are 0.05% by weight to 0.5% by weight, for example 0.1% by weight, 0.01% by weight to 0.2% by weight, for example 0.05% by weight, 0.01% by weight to 0.2% by weight, for example 0.05% by weight, 0.05% by weight to 0.2% by weight, for example 0.05% by weight, respectively, relative to the total weight of the semiconductor particles made of strontium titanate doped with magnesium and scandium. EXAMPLES

[0032] Several examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples.

[0033] The following experiments were carried out in Examples 1 to 10 and Comparative Examples 1 to 3. The experiments were carried out with N=3, and the error bars shown in Figures 1 and 3 indicate standard deviation.

[0034] Example 1 1.Mixing raw powders The raw material powders of strontium titanate (SrTiO3), scandium oxide (Sc2O3) at 1 mol % as Sc relative to the total number of moles of the strontium titanate, magnesium oxide (MgO) at 0.5 mol % as Mg relative to the total number of moles of the strontium titanate, and strontium chloride solvent (SrCl2) at 1000 mol % relative to the total number of moles of the strontium titanate were added to an agate mortar and mixed in the mortar for 30 minutes.

[0035] 2. Firing (Flux method) The mixture mixed in "1. Mixing of raw powders" was transferred to an alumina crucible and heated to 1200°C over 3 hours. After being held at 1200°C for 30 minutes, it was allowed to cool to room temperature over 6 hours. After cooling, distilled water was added to the alumina crucible, and the contents stuck to the wall of the alumina crucible were removed by stirring while applying ultrasonic waves with an ultrasonic stirrer. The contents peeled off from the alumina crucible were subjected to suction filtration and washed with distilled water. At this time, washing was performed until the pH of the washing solution that had passed through the contents became 7 and the washing solution did not contain any chlorine. Note that pH was confirmed using pH test paper, and the presence or absence of chlorine was confirmed by adding 0.1 mol / L (M) silver nitrate to the washing solution and confirming that silver chloride was not generated. After washing, the contents were dried at 70°C. Note that elemental analysis (ICP-MS) was used to confirm that the dried product was strontium titanate containing the desired doping amounts of magnesium and scandium.

[0036] 3. Addition of surface modification raw materials as co-catalysts and support by light irradiation (photoelectrodeposition) 100 mg of the photocatalyst powder obtained in "2. Firing (Flux method)" was placed in a reaction glass vessel (Pyrex (registered trademark)) and 100 mL of distilled water was added thereto using a measuring cylinder. After thoroughly dispersing the photocatalyst powder in the distilled water by applying ultrasonic waves for 1 minute, an aqueous solution of rhodium chloride (RhCl3) was added so that Rh was 0.1% by weight relative to the total weight of the photocatalyst, and the top of the reaction vessel was covered with a quartz plate.

[0037] The obtained dispersion was irradiated with light from a xenon lamp (300 W, 20 A) for 10 minutes under atmospheric pressure conditions. Next, a K2CrO4 aqueous solution was added so that Cr was 0.05 wt% based on the total weight of the photocatalyst, and light was irradiated for 5 minutes under the same conditions as above. Finally, a Co(NO3)2 aqueous solution was added so that Co was 0.05 wt% based on the total weight of the photocatalyst, and light was irradiated for 60 minutes under the same conditions as above.

[0038] 4. Quantum Efficiency Measurement The glass container containing the dispersion liquid containing the photocatalyst obtained in "3. Addition of surface modification raw material as a cocatalyst and support by light irradiation (photoelectrodeposition)" was connected to a vacuum pump to degas it, and then filled with argon gas. The glass container was connected to a gas chromatograph via glass piping, and the dispersion liquid containing the photocatalyst in the glass container was irradiated with light from a xenon lamp (300 W, 20 mA) through a 365 nm or 310 nm band pass filter, causing a water splitting reaction to generate hydrogen gas. To detect the amount of hydrogen gas generated, the hydrogen gas generated in the glass piping was stored during the two hours of light irradiation, and the stored gas was introduced into the gas chromatograph to detect the amount of hydrogen gas (measurement was performed once every 20 minutes). For the detection of the amount of hydrogen gas in the chromatograph, a calibration curve between the number of moles of hydrogen and the area of ​​the detection data portion corresponding to hydrogen gas was created in advance using a standard gas with a known number of moles of hydrogen gas, and the number of moles generated was determined from the area of ​​the detection data portion of the hydrogen gas introduced into the gas chromatograph from the glass pipe using the calibration curve. Meanwhile, for the number of photons irradiated to the photocatalyst dispersion in the glass container, the wattage P (amount of energy per unit time) of the total light irradiated to the photocatalyst dispersion in the glass container used for the measurement was measured with a photodiode sensor, and the number of photons I incident on the photocatalyst dispersion per unit time was calculated using the following formula. I( / s)=P(W)×λ(m) / [h(J·s)×c(m / s)] In the formula, λ is the wavelength of the illuminating light, h is Planck's constant, and c is the speed of light. The quantum efficiency was calculated according to the following formula. Quantum efficiency (%) = n ( / s) × NA × 2 / I × 100 In the formula, n is the number of moles of hydrogen gas generated per unit time, and N is Avogadro's number.

[0039] Example 2 In Example 1, the experiment was carried out in the same manner as in Example 1, except that the raw material powders used were strontium titanate (SrTiO3), scandium oxide (Sc2O3) with 0.5 mol % as Sc relative to the total number of moles of the strontium titanate, magnesium oxide (MgO) with 0.5 mol % as Mg relative to the total number of moles of the strontium titanate, and strontium chloride solvent (SrCl2) with 1000 mol % relative to the total number of moles of the strontium titanate.

[0040] Example 3 In Example 1, the experiment was carried out in the same manner as in Example 1, except that the raw material powders used were strontium titanate (SrTiO3), scandium oxide (Sc2O3) with 1.5 mol % as Sc relative to the total number of moles of the strontium titanate, magnesium oxide (MgO) with 0.5 mol % as Mg relative to the total number of moles of the strontium titanate, and strontium chloride solvent (SrCl2) with 1000 mol % relative to the total number of moles of the strontium titanate.

[0041] Example 4 In Example 1, the experiment was carried out in the same manner as in Example 1, except that the raw material powders used were strontium titanate (SrTiO3), scandium oxide (Sc2O3) with 2 mol % as Sc relative to the total number of moles of the strontium titanate, magnesium oxide (MgO) with 0.5 mol % as Mg relative to the total number of moles of the strontium titanate, and strontium chloride solvent (SrCl2) with 1000 mol % relative to the total number of moles of the strontium titanate.

[0042] Comparative Example 1 In Example 1, the experiment was carried out in the same manner as in Example 1, except that the raw material powders used were strontium titanate (SrTiO3), magnesium oxide (MgO) at 0.5 mol % as Mg relative to the total number of moles of the strontium titanate, and strontium chloride solvent (SrCl2) at 1000 mol % relative to the total number of moles of the strontium titanate.

[0043] Comparative Example 2 The experiment was carried out in the same manner as in Example 1, except that the raw material powders used were strontium titanate (SrTiO3), aluminum oxide (Al2O3) with 2 mol% Al relative to the total number of moles of the strontium titanate, and strontium chloride solvent (SrCl2) with 1000 mol% relative to the total number of moles of the strontium titanate.

[0044] Comparative Example 3 In Example 1, the experiment was carried out in the same manner as in Example 1, except that the raw material powders used were strontium titanate (SrTiO3), scandium oxide (Sc2O3) with 2 mol % as Sc relative to the total number of moles of the strontium titanate, aluminum oxide (Al2O3) with 2 mol % as Al relative to the total number of moles of the strontium titanate, and strontium chloride solvent (SrCl2) with 1000 mol % relative to the total number of moles of the strontium titanate.

[0045] Example 5 In Example 1, the experiment was carried out in the same manner as in Example 1, except that the raw material powders used were strontium titanate (SrTiO3), scandium oxide (Sc2O3) with 1 mol % as Sc relative to the total number of moles of the strontium titanate, magnesium oxide (MgO) with 0.5 mol % as Mg relative to the total number of moles of the strontium titanate, and strontium chloride solvent (SrCl2) with 1000 mol % relative to the total number of moles of the strontium titanate.

[0046] Example 6 In Example 1, the experiment was carried out in the same manner as in Example 1, except that the raw material powders used were strontium titanate (SrTiO3), scandium oxide (Sc2O3) at 1 mol % as Sc relative to the total number of moles of the strontium titanate, magnesium oxide (MgO) at 1 mol % as Mg relative to the total number of moles of the strontium titanate, and strontium chloride solvent (SrCl2) at 1000 mol % relative to the total number of moles of the strontium titanate.

[0047] Example 7 In Example 1, the experiment was carried out in the same manner as in Example 1, except that the raw material powders used were strontium titanate (SrTiO3), scandium oxide (Sc2O3) with 1 mol % as Sc relative to the total number of moles of the strontium titanate, magnesium oxide (MgO) with 2 mol % as Mg relative to the total number of moles of the strontium titanate, and strontium chloride solvent (SrCl2) with 1000 mol % relative to the total number of moles of the strontium titanate.

[0048] Example 8 In Example 1, the experiment was carried out in the same manner as in Example 1, except that the raw material powders used were strontium titanate (SrTiO3), scandium oxide (Sc2O3) with 1 mol % as Sc relative to the total number of moles of the strontium titanate, magnesium oxide (MgO) with 5 mol % as Mg relative to the total number of moles of the strontium titanate, and strontium chloride solvent (SrCl2) with 1000 mol % relative to the total number of moles of the strontium titanate.

[0049] Example 9 In Example 1, the experiment was carried out in the same manner as in Example 1, except that the raw material powders used were strontium titanate (SrTiO3), scandium oxide (Sc2O3) with 1 mol % as Sc relative to the total number of moles of the strontium titanate, magnesium oxide (MgO) with 8 mol % as Mg relative to the total number of moles of the strontium titanate, and strontium chloride solvent (SrCl2) with 1000 mol % relative to the total number of moles of the strontium titanate.

[0050] Example 10 In Example 1, the experiment was carried out in the same manner as in Example 1, except that the raw material powders used were strontium titanate (SrTiO3), scandium oxide (Sc2O3) with 1 mol % as Sc relative to the total number of moles of the strontium titanate, magnesium oxide (MgO) with 10 mol % as Mg relative to the total number of moles of the strontium titanate, and strontium chloride solvent (SrCl2) with 1000 mol % relative to the total number of moles of the strontium titanate.

[0051] Figure 1 shows the results of the quantum efficiency for Example 1 and Comparative Examples 2 and 3. It is clear from Figure 1 that the quantum efficiency is improved by using magnesium together with scandium as a doping element for strontium titanate.

[0052] Figure 2 shows the results of quantum efficiency for Examples 1 to 4 and Comparative Example 1. It was found from Figure 2 that the molar ratio of scandium and magnesium as doping elements for strontium titanate is preferably 1:1 to 1:4, and more preferably 1:2.

[0053] Figure 3 shows the quantum efficiency results for Examples 5 to 10. It was found from Figure 1 that the amount of magnesium as a doping element in strontium titanate is preferably 0.5 mol % to 5 mol %, and more preferably 0.5 mol % to 2 mol %, in terms of Mg, relative to the total weight of strontium titanate.

[0054] Figure 4 shows scanning electron microscope (SEM) photographs of the crystals of Example 1 and Comparative Example 3. As can be seen from Figure 4, no nanostep structure was observed in the aluminum- and scandium-doped strontium titanate crystal of Comparative Example 3, but a nanostep structure formed by exposing the 100-plane of the crystal was observed in the magnesium- and scandium-doped strontium titanate crystal of Example 1. The average width of 20 steps in the nanostep structure was measured to be 10 nm.

Claims

1. A water-splitting photocatalytic material comprising strontium titanate, the strontium titanate being doped with magnesium and scandium.

2. 2. The water splitting photocatalytic material according to claim 1, wherein the molar ratio of doped magnesium to scandium is 1:1 to 1:

4.

3. 2. The water splitting photocatalytic material according to claim 1, wherein the molar ratio of doped magnesium to scandium is 1:

2.

4. 2. The water splitting photocatalyst material according to claim 1, wherein the total doping amount of magnesium and scandium is 0.1 mol % to 10 mol % based on the total moles of strontium titanate.

5. 2. The water splitting photocatalyst material according to claim 1, wherein the magnesium- and scandium-doped strontium titanate has a nanostep structure formed by exposing only the 100-facet, and the average step width of the nanostep structure measured by SEM is 5 nm to 20 nm.

6. A method for producing a water splitting photocatalyst material according to any one of claims 1 to 5, comprising mixing strontium titanate, scandium oxide and magnesium oxide in strontium chloride, calcining the mixture and then washing the mixture.

7. 6. A water-splitting photocatalyst comprising the water-splitting photocatalyst material according to claim 1 and a co-catalyst added to the particle surfaces of the water-splitting photocatalyst material.

Citation Information

Patent Citations

  • Production method of core-shell type photocatalyst, core-shell type photocatalyst, and water splitting method using core-shell type photocatalyst

    JP2015071128A

  • Strontium titanate particle, method for producing strontium titanate particle, photocatalyst forming composition, photocatalyst, photocatalyst film, and structure

    JP2019130509A

  • Semiconductor particle used for water decomposition photocatalyst, photocatalyst using the same and method for synthesizing them

    JP2023051595A